GUIDELINES - Interpreting and companion serivces models to facilitate access to health services for Francophone and Acadian minoritycommunities (INTACC) - Bowen, sarah; Renée, Chartier; Richard, Lise (2016)
These guidelines were written as a guide for service providers to gain an understanding of the competencies, roles, responsibilities, and limits of interpretation and accompaniment services. They also lay out an Interpreters’ Code of Ethics. The document was prepared for the Société Santé en français’ INTACC